Exploring the Critical Success Criteria and Factors of Adopting Technological Innovation in the U.A.E Public Sectors - Al Marzooqi, Hanan Ibrahim Ahmed (2016)
Government in the United Arab Emirates stimulates the public sectors to provide intelligent and innovative services to the public users. However, as the concept of innovation in public services is considered a new topic for the U.A.E government, most of the departments need to be aware of the critical success criteria and factors for innovation projects. This research asserts the great importance of implementing innovation in projects in general and in the public sector specifically. It examines the variables that contribute to project success and failure in details. Those variables are known as project success criteria and factors. This paper explains the effects of each of those variables in project success and failure, besides the effect of organization, project team members and users in those variables. The researcher in this paper investigates the relationship between both variables and how both of them lead to project success or failure. Quantitative methods are implemented to evaluate the research variables and explain the significant effect of project criteria and project factors on the success or failure of innovative projects through 20 federal government departments in U.A.E. The research findings highlight that the most important factor in project success for the innovative projects across the twenty (20) federal departments in U.A.E is the strategy of innovative projects. The findings support the idea that the U.A.E government spends most of their times to improve the project strategies and deliver the service on the assigned times. In addition, managerial supports for the innovative projects in the U.A.E federal department succeeded to increase the level of satisfactions for the project team members. Moreover, the success of innovative projects through the selected organization in the U.A.E depends on open communication as these factors help the organization to understand the user’s demands and to provide suitable innovative services to achieve high levels of users’ satisfactions.